Catalytic oxidation of 3,5-di-tertbutyl catechol (3,5-DTBC) and 2,6-di-tertbutyl phenol (2,6-DTBP) by copper(II) and cobalt(II) complexes of a binucleating tetrapyrrole macrocycle - Francis V. ACholla; Kristin B. Mertes (Bulletin of the Chemical Society of Ethiopia, 1989)
Bull. Chem. Soc. Ethiop., 3(1), 17-24 (1989).